Heterologous microsatellite primer pairs informative for the whole genus Arachis - Hoshino, Andrea Akemi [UNESP]; Bravo, Juliana Pereira [UNESP]; Angelici, Carla M.L.C.D. [UNESP]; Barbosa, Andréa V. Gobbi [UNESP]; Lopes, Catalina Romero [UNESP]; Gimenes, Marcos A. [UNESP] (Sociedade Brasileira de Genética, 2006)
The genus Arachis currently comprises 69 described species, some of which have potential and real value as human and animal foods. These Arachis species have been collected and maintained in germplasm banks to provide material that can be used as sources of genes in breeding programs and for the selection of new cultivars. One of the principal objectives of germplasm conservation is the evaluation of genetic variability, which is best conducted using molecular markers. We investigated the use of heterologous primers to amplify microsatellite loci that could be used to evaluate genetic variability in Arachis germplasm. Fifteen microsatellite primer pairs were tested in 76 accessions of 34 species from the nine Arachis sections. The data indicated that heterologous primers were very useful in Arachis since they had high transferability among the species (91%) and allowed the amplification of very polymorphic putative loci, which allowed both the characterization of most accessions and to make inferences about the mating systems of some species analyzed. Our data also revealed that the germplasm analyzed showed high variability, even when represented by few accessions.
Keywords: peanut; genetic relationship; molecular markers; wild relatives